Religious literacy for responding to violence and abuse involves the capacity to go beyond stereotypes. Issue 2 (14th May 2018) - Crisp, Beth R.; Epstein, Sarah; Afrouz, Rojan; Taket, Ann
Abstract : Purpose: There is an increasing recognition that health and social care professionals require the knowledge and skills to negotiate religious beliefs and cultures but as yet there is little understanding as to what this entails. The purpose of this paper is to explore what religious literacy means in regard to protecting children from sexual assault in Australia's Jewish community and Muslim women who experience domestic violence. Design/methodology/approach: Drawing on two ongoing research studies, this paper provides an overview of the diverse perspectives found in the literature on child sexual assault in Jewish communities and Muslim women's experiences and responses to domestic violence. Findings: Individual and community attitudes and responses to child sexual assault and domestic violence do not fit stereotypes either within or beyond religious communities. Hence, educating for religious literacy needs to ensure stereotypes are recognised as undue simplifications of the truth, and failure to understand this can result in harm. Furthermore, religious literacy is important for health and social care workers if they are to effectively engage with the leadership of religious communities to change community attitudes. Originality/value: This paper draws together common issues around the need for religious literacy when working with Jewish and Muslim communities in addressing issues of abuse and violence.